To determine which equation you would first divide both sides by 6 and then add 8 to both sides, let's analyze each option step by step.
-
8(x − 6) = 48
- Dividing both sides by 6 won't help simplify this equation in the context of your steps.
-
6(x + 8) = 48
- Dividing both sides by 6 gives: x + 8 = 8. After that, you would subtract 8 (not add it), so this does not fit your order of steps.
-
6x − 8 = 48
- Dividing both sides by 6 gives: x - (4/3) = 8. Then you would need to add 8 after that.
-
6(x − 8) = 48
- Dividing both sides by 6 gives: x - 8 = 8. Then you would add 8: x = 16.
The correct option based on the requirement of dividing first by 6 and then adding 8 to both sides would be 6(x − 8) = 48.